Design and implementation of EMRC web-based portal - Mallo-Eustaquio, Geraldine G. (2018)
The Educational Media Resource Center (EMRC) Web-Based Portal's design and implementation was proposed and described in this paper. Rapid Application Development (RAD) was the methodology used to described the systematic approach of the development. The web portal was developed using programming platforms such as HTML, CSS, Javascript, and PHP the frontend of the system and MySQL was used for its database. The model of the web portal was designed using the Unified Modeling Language (UML) which includes use-case diagram, activity diagram and class diagram. EMRC web-based portal was tested and evaluated with the checklist type questionnaire incorporating the standard of ISO 25010:2011.